Project Management in the Fourth Industrial Revolution (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional De Tecnología, Ciencia Y Sociedad, 2021)
The Fourth Industrial Revolution (also referred to as Industry 4.0) is driven by a massive utilization of new technologies, such as robots, artificial intelligence, Internet of Things (IoT), Big Data, Quantum Computing and Quantum Communications, replacing humans by machines in certain tasks or the development of new or more efficient tasks. The Fourth Industrial Revolution is originating huge modifications in society and organizations. Human adaptation to the new paradigm is required, as it will have a high impact on jobs and on the required skills.